The Role of Moral Foundations and Attitudinal Motivations in the Chinese's Support for China’s Vaccine Diplomacy During the COVID-19 Pandemic - Xiao Wang (Journal of Current Chinese Affairs, 2023)
During the COVID-19 pandemic, China has been the leading exporter and donor of COVID-19 vaccines in the world. Based on a survey of 460 Chinese participants conducted in mainland China in March 2021, the results showed that the participants’ value-expressive attitudes (i.e. their responsibility to help) and esteem attitudes (i.e. China's image and status) were strong predictors of their support for vaccine exports and donations, whereas attitudes related to prevention and a possible vaccine shortage in China were weak predictors. Fairness and ingroup loyalty were the major moral foundations of their support for such international efforts; the influence of fairness and ingroup loyalty was both direct and mediated by value-expressive and esteem attitudes. Collectively, the present results show that support for international efforts can be analysed from a moral, altruistic perspective and thus extend the previous theorising that focused on the transactional nature of international outreach efforts.